The Effect of Scapula Supporting Pillow on Pulmonary Function and Postural Changes in Individuals With Thoracic Kyphosis - Woosuk Lim; Ilyoung Moon; Wookyung Sung; Chung-hwi Yi (Physical Therapy Korea)
Background: The widespread use of smartphones and personal computers has contributed to a rise in thoracic kyphosis, a condition characterized by excessive outward curvature of the upper back. This condition can lead to reduced lung function, poor posture, and decreased spinal angles, all of which can cause reductions in forced vital capacity (FVC) and forced expiratory volume in 1 second (FEV1). Furthermore, these issues are often associated with scapular protraction and anterior tilting. Objects: This study aimed to investigate the effects of using a scapular support pillow in people with thoracic kyphosis, as well as determine the changes in respiratory capacity and postural alignment. Methods: Forty-one participants (25 males and 16 females) with thoracic kyphosis (Cobb angle > 40°) were included in the study. Their respiratory function (FVC, FEV1) and body posture (spinal angle, chest expansion, acromion-to-the-wall index) were measured before and after using the scapular support pillow for approximately 30 minutes. FVC, FEV1, spinal angle, chest expansion, and acromion-to-the-wall index were analyzed using paired-t test. The level of statistical significance was set at p < 0.05. Results: The results demonstrated significant improvements in all measured parameters. Both respiratory function and posture-related metrics showed notable increases after using the scapular support pillow. Conclusion: The use of a scapular support pillow can effectively improve respiratory function and postural alignment in patients with thoracic kyphosis. Our research makes a meaningful contribution by proposing an effortless and convenient treatment option for individuals with thoracic kyphosis.